2002
DOI: 10.1007/bf03218321
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification studies by atomic force microscopy for Ar-plasma treated polyethylene

Abstract: Atomic force microscopy(AFM) was used to study the polyethylene(PE) surfaces grafted and immobilized with acrylic acid by Ar plasma treatment. The topographical images and parameters including RMS roughness and Rp-v value provided an appropriate means to characterize the surfaces. The plasma grafting and immobilization method were a useful tool for the preparation of surfaces with carboxyl group. However, the plasma immobilization method turned out to have a limitation to use as a means of preparation of PE su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Surface chemical modification can be performed through the surface grafting, onto polymer films, of suitable monomers containing functional groups that can be used for further reactions. In this way, functional groups such as amine, imine, hydroxyl, carboxylic acid, sulfate, and epoxy groups can be incorporated onto the surface of a broad range of conventional polymeric substrates, most of which have a nonpolar, less reactive surface 11. Surface grafting may proceed by free‐radical mechanisms generated by oxidants such as Ce +4 ions12 and peroxide initiators 13.…”
Section: Introductionmentioning
confidence: 99%
“…Surface chemical modification can be performed through the surface grafting, onto polymer films, of suitable monomers containing functional groups that can be used for further reactions. In this way, functional groups such as amine, imine, hydroxyl, carboxylic acid, sulfate, and epoxy groups can be incorporated onto the surface of a broad range of conventional polymeric substrates, most of which have a nonpolar, less reactive surface 11. Surface grafting may proceed by free‐radical mechanisms generated by oxidants such as Ce +4 ions12 and peroxide initiators 13.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 The surface treatment of the chemical compounds in silicon rubber or vulcanized rubber is usually performed by using a glow discharge or a corona discharge. 2,6,7 Modifying a polymer surface of a low-temperature plasma through glow discharge or corona discharge does not directly influence the characteristics of the polymer material itself; only the modification of the surface layer is capable of having that effect. The use of an excimer laser is a dry process, compared to the others that are generally wet, and it not only simplifies the surface modification process but it also saves water resources that are used largely for cleaning the surface.…”
Section: Introductionmentioning
confidence: 99%
“…This energy transfer process continues until one of the atoms is knocked out into the vapor phase. In our previous study, 10,11 we reported that ablation played an important role to decrease hydrophilic surface properties and surface topographies for the immobilized poly(ethylene) (PE) surfaces with acrylic acid by Ar plasma.…”
Section: Introductionmentioning
confidence: 99%